Effects of panax ginseng root powder supplementations into layer quail diets on egg yield, external and internal quality traits, hatchability and blood parameters - Ulger, İ; Para, G; Sinmez, ÇÇ; Ayasan, T (Journal of the Hellenic Veterinary Medical Society, 2025)
This study was conducted to investigate the effects of Panax ginseng (G) root powder supplementations into layer quail diets on egg yield, egg quality traits, hatchability and blood serum parameters. In present trials, 144 quail (108 female and 36 male) were used. Experiments were composed of two groups: control and ginseng-supplemented groups. Each group had 3 sub-groups and each sub-group had 6 replicates. Panax ginseng supplementations did not have significant effects on egg yield and feed consumptions (p > 0.05). Except for the 7th week of the experiments, ginseng treatments did not have significant effects on feed conversion ratios (p < 0.05). Effects of ginseng supplementations on eggshell thickness were not found to be significant (p < 0.05). Except for the 6th week and general means, ginseng treatments did not have any significant effects on shell ratio (p > 0.05). Differences in hatchability parameters (hatchability, hatching power, fertility rate, hatching live weight and first week live weight) were not found to be significant. Finally, it was concluded based on present findings that Panax ginseng root powder supplementations into layer quail diets may improve some performance parameters and egg quality traits, but further research is needed to prove such outcomes for other poultry species.